A Modern Encryption Approach to Improve Video Security as an Advanced Standard Adopted - Al-Khafaji, Baydaa Jaffer; Monem S. Rahma, Abdul (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
While transmitting data across a network, it is important to keep in mind that some fields may contain sensitive information. One of the most pressing concerns, then, is the protection of private information. The confidentiality and integrity of an online video are the primary concerns of the suggested approach in this work. Video compression using Moving Picture Experts Group (MPEG), video encryption, and video decryption are the three components that make up the proposed study. The data is encrypted using one of the most used block cipher algorithms, the Advanced Encryption Standard (AES) technique. The real-time needs of frame decoding can be satisfied by a software implementation. Our research leads us to believe that this has the potential for use in safe, real-time video transmission. In this case, the compressed domain is where the video stream encryption takes place. As a result, the compression and decompression time cycles are maintained. Because of this, it is able to cut encryption time by 90% compared to the method that encrypts the entire video. However, the most bits that can be encrypted using this method are 128 bits. As a result, far fewer calculations are needed to get satisfactory encryption results. The software solution has to be fast enough for frame decoding to work in real time. Based on our findings, this might be utilized for secure, real-time video communication. We are applying the C++ programming language for coding.